Regulating artificial intelligence and robotics: ethics by design in a digital society. Issue 2 (15th March 2021) - Iphofen, Ron; Kritikos, Mihalis
ABSTRACT: Evidence-based policymaking must urgently consider regulations addressing advances made in artificial intelligence (AI) and robotics, as well as issues of ownership, management and control. Many repetitive manufacturing tasks once requiring human labour have already been replaced by robots. The general public are facing associated risks to safety and privacy with the appearance of drones, driverless cars, robots of care, and human repair and enhancement. Major challenges for policymakers arise as machines acquire the ability to learn and become autonomous in their decision making. When independent of the humans that created them, their true 'intelligence' is tested in terms of their status as 'moral beings'. Given their algorithmic decision making, questions arise about how 'they' could make ethical decisions about their actions and interactions with humans. This paper reviews current issues raised about the morality of autonomous learning machines and explores whether policy can be developed to address their potential to acquire a moral status. The authors argue that policies and regulations will fail if no account is taken of the ethics of robotics, either to ensure an 'ethics by design' or prevent them from becoming 'autonomous moral agents'.